Synthesis of polyethylene glycol-functionalized multi-walled carbon nanotubes with a microwave-assisted approach for improved heat dissipation1. Issue 45 (20th May 2015) - Amiri, Ahmad; Sadri, Rad; Ahmadi, Goodarz; Chew, B. T.; Kazi, S. N.; Shanbedi, Mehdi; Sadat Alehashem, Maryam
<x xml:space="preserve">Abstract</x> In order to improve the dispersibility of multi-walled carbon nanotubes (MWCNT) in aqueous media, MWCNT were functionalized with tetrahydrofurfuryl polyethylene glycol (TFPEG) in a one-pot, fast and environmentally friendly method.